The Peculiarities of Obtaining a Parents Consent (Legal Representative’s) to the Departure of a Minorfrom the Russian Federation - Y. O. Petrova (Сибирское юридическое обозрение, 2019)
The analysis of the current legislation regulating the procedure for the entry and exit of minors outside the Russian Federation has been carried out, the features of obtaining consent for the departure of a minor outside the Russian Federation have been noted. The necessity of notarization of such consent has been investigated, judicial decisions on this issue have been considered, and the legal norms governing the form of withdrawal of consent to a minor’s departure have been examined. The author has formulated proposals to improve the current legislation governing the entry and exit of minors outside the Russian Federation, including legislatively stating the obligation of the person who has withdrawn consent to leave the minor, to inform the interested person and the minor himself about such actions within a reasonable time.